Ah Khaw Goes To Heaven (AKGTH): initiating culturally responsive teaching and identity construction in the Malaysian classrooms - Idrus, Faizah (2013)
This article presents evidence to the need for culturally responsive teaching in the Malaysian classrooms. Students who come from culturally diverse community as well as those who are in almost homogeneous backgrounds need to learn to function effectively in multicultural Malaysia. Since an important objective of education is to prepare individuals to exercise efficaciously in their environment, all students in multicultural society could benefit from exposure to Culturally Responsive Teaching (Gay, 2000) and learning, as tensions between races had erupted easily in the last five years (Idrus, 2012). The text teachers used in this study was AKGTH by A. Samad Ismail. A qualitative inquiry employing semi-structured, in depth interviews with 7 English language teachers in 5 schools around Kuala Lumpur were carried out. Classrooms observations were conducted, and group interviews with 6 groups of students were also carried out. Thematic analysis were performed and the findings suggest that students’ interpretation of CRT were influenced by an orthodox perception of their identity in the classroom and in the teaching and learning process, while teachers were more skeptical and reserved in developing CRT. From teachers and students reactions to questions elicited from AKGTH, it is evident that they were not ready for CRT. Through this small-scale research, it is now timely to rigorously introduce and develop CRT in the Malaysian classrooms in which curriculum developers and teacher professional development have to take into serious consideration in the quest for a more integrated, unified society.